Book Review: Cognitive linguistics and religious language an introduction - Yunita Laila Zulfa; Frida Akmalia (Indonesian Reseacher for Language Learning and Teaching, 2024)
Since the emergence of modern humans, religion has become one of the basic human frameworks to determine the position of humanity in the world (Rossano, 2006). There are many ways to investigate religious behavior and thought. One of them is using language as the key approach because it is the center of religious behavior in terms of interaction with supernatural agents, theological rationalization, normative discourse, or rituals (Downes, 2011). For example, the verse on light taken from the Qur'an (24:35), describes a Muslim's experience of divinity, which may be difficult to articulate. But with the right language, this can be an intermediary for humans to understand it. Language is the most detailed window that can be used to know how people think. However, sometimes individuals cannot explain the mental models and cognitive patterns of the language they use, so there is a sub-field in language called Cognitive Linguistics to describe it. This book is intended to serve as an introduction to the current research of cognitive linguistics in religious languages as well as to explain how cognitive linguistic approaches are being used in the study of modern religious languages.